Islamic Tradition and Digital Resistance: Constructing Moderate Religious Habitus in Indonesian Pesantren Salaf - Saepudin, Ahmad; Rohandy, Fajar (Tashwirul Afkar, 2024)
This study aims to explore how traditional religious practices collectively performed in pesantren Salaf contribute to shaping moderate religious conduct within the Nahdliyin community. Employing a qualitative approach, data were collected through participatory observation, in-depth interviews, and visual documentation in pesantren across Bandung, Purwakarta, and Bekasi, and were subsequently analysed thematically. The main findings reveal that practices such as tahlilan, maulid celebrations, grave visitation (ziarah kubur), and classical Islamic book recitations (pengajian kitab kuning) serve not only as ritual expressions but also as mechanisms for the internalisation of spiritual and social values. These values, in turn, construct an inclusive, civilised, and contextual religious habitus. The pesantren also demonstrate adaptive resistance to puritan digital preaching trends by developing content rooted in sanad (religious authority chains) and media literacy grounded in traditional teachings. The implications of this research underscore the significance of preserving religious traditions as a strategy for character education and culturally-based religious deradicalisation. The study’s original contribution lies in its integration of religious tradition, the theory of religious habitus, and digital responses of pesantren as mediating actors within the contemporary Islamic landscape in Indonesia.